The Success of Diversion For Children Who In Conflict With The Law On Investigation Level - Supusepa, Reimon; Sopacua, Margie Gladies (SASI, 2023)
Introduction: The SPPA Law is a regulation that applies restorative justice and diversion as an effort to divert cases from litigation to non-litigation. Children as perpetrators of criminal acts in the process of resolving criminal cases must be diversified at the police (investigation), prosecutor's office, and court levels.Purposes of the Research: The purpose of this research is to find new ideas and discuss the success of diversion at the investigation stage for juvenile offenders.Methods of the Research: This research is normative research, the type of research is descriptive analytical. The sources of legal materials used in this study are primary legal materials and secondary legal materials. The technique of collecting legal materials used in this writing was carried out by means of library research on legal materials, both primary legal materials, secondary legal materials, and analysis of legal materials used by the author is descriptive qualitative which identifies the primary and secondary legal materials used. will be carried out in analyzing problems in a series of processing stages by carrying out an inventory, systematization, to make it easier to analyze these problems.Results of the Research: Based on the problems studied, the authors found several new ideas about the success of diversion at the level of investigation which were influenced by several factors including 1) the victim factor where the victim was willing to forgive the perpetrator's actions; 2) the actor's factor where the perpetrator is willing to agree to compensation that has been agreed upon with the victim; 3) the Investigative factor, namely the role of the pro-active investigator as a facilitator in seeking maximum diversion and opening a space for peace between the perpetrator and the victim; 4) the factor of freedom in which the Children's Community Guidance Resources who understand their role as diversion facilitators maximally want to provide assistance to children in an effort to make peace between perpetrators and victims; 5) the family factor, namely the victim's family who wants peace and influences the victim to make peace with the perpetrator and 6) the community factor where the role of the community in this case is represented by community leaders, traditional leaders, or religious leaders as facilitators in efforts to settle peace between the perpetrators and victims of crime